2016
DOI: 10.1016/j.ijsu.2016.08.524
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy versus laparotomy for the management of penetrating abdominal trauma: A systematic review and meta-analysis

Abstract: Our analysis of best available evidence mainly from heterogeneous observational studies has demonstrated that laparoscopic evaluation of haemodynamically stable patients with PAT may be safe and can reduce post-operative complications and length of hospital stay. The most important advantage of laparoscopy is avoidance of non-therapeutic laparotomies which are associated with considerable morbidity. However, no definitive conclusion can be made regarding the therapeutic role of laparoscopy in PAT based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 22 publications
3
56
1
7
Order By: Relevance
“…As familiarity with the technique of laparoscopy improved, so too did its sensitivity . A recent systematic review and meta‐analysis described a rate of missed injury of 118/1604 patients (7.4%), with all missed injuries being reported in studies published prior to 2010 . The majority of included studies reported a 100% sensitivity for ruling out abdominal visceral injury .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As familiarity with the technique of laparoscopy improved, so too did its sensitivity . A recent systematic review and meta‐analysis described a rate of missed injury of 118/1604 patients (7.4%), with all missed injuries being reported in studies published prior to 2010 . The majority of included studies reported a 100% sensitivity for ruling out abdominal visceral injury .…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta‐analysis described a rate of missed injury of 118/1604 patients (7.4%), with all missed injuries being reported in studies published prior to 2010 . The majority of included studies reported a 100% sensitivity for ruling out abdominal visceral injury . Diagnostic laparoscopy was reported to avoid non‐therapeutic laparotomy in 45.6% of patients …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 1960s, Shaftan first challenged the idea of mandated laparotomies for abdominal trauma with his term of selective conservatism, as half of his patients with penetrating abdominal trauma did not require operative repair [2]. In recent review, surgical exploration in the setting of penetrating abdominal trauma has been associated with negative laparotomy rates of about 61% [3]. Negative or non-therapeutic laparotomies are associated with 20% morbidity rate [4].…”
Section: Introductionmentioning
confidence: 99%